THE INFLUENCE OF ENGLISH PROSE ON TRANSFORMING LIFE TRUTH INTO ARTISTIC REALITY AND THE POETICS OF THE CONTEMPORARY UZBEK NOVEL - Atakulova Shahlo Shamidullaevna (JOURNAL OF NEW CENTURY INNOVATIONS, 2025)
This article explores the transformative influence of English prose, particularly from the 20th century, on the development of the poetics of the contemporary Uzbek novel. It examines how English literary traditions have contributed to the artistic reinterpretation of life truth in modern Uzbek literature. Drawing from comparative literary studies, structural poetics, and narrative philosophy, the article investigates the intertextual dialogues between English and Uzbek prose traditions. The discussion pays particular attention to the stylistic, thematic, and ideological parallels that emerge through this interaction, focusing on how Uzbek novelists construct artistic reality through symbolic naming, chronotopic framing, and existential motifs.